Pengaruh Financial Knowledge, Financial Attitude Dan Locus Of Control Terhadap Financial Management Behavior (Studi Kasus Pada Peternak Ayam Desa Arjowilangun Kecamatan Kalipare) - Riza Eka Pratama; Muhammad Agus Salim; Achmad Agus Priyono (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract The purpose of this research is to determine and analyze the Financial Management Behavior of chicken farmers in Arjowilangun Village in 2022. In measuring this variable, the independent variables used to influence are financial knowledge, financial Attitude and Locus of Control variables. The type of research used is explanatory research, which means explaining the causal relationship between the independent variable and the dependent variable. The method used in managing the data uses a quantitative approach with multiple linear regression analysis tools through the SPSS program. The data used are primary data as well as secondary data obtained by using interview techniques, questionnaires, and direct observation. According to data from the Head of the Sustainable Chicken Livestock Group, Arjowilangun Village in 2022, the population obtained is 80 farmers. Furthermore, simple random sampling and using the Slovin formula is the technique used in determining the number of samples as many as 66 samples. From data management, it was found that partially financial knowledge had a positive and significant effect on financial management behavior of chicken farmers in Arjowilangun Village, financial Attitude had a positive and significant impact on financial management behavior of chicken farmers in Arjowilangun Village and locus of control had a positive effect. and significant to the financial management behavior of chicken farmers in Arjowilangun Village. Keywords: Financial Management Behavior, Financial Knowledge, Financial Attitude, Locus of Control, Chicken Farmers.